EMBALAGENS PARA SORVETES – UM RECURSO DIGITAL PARA O ENSINO MÉDIO - SOARES, CARINE G. T.; BITENCORT, CRISTIANE B.; KONAGESKI, DIONATAN M. F.; EICKHOFF, FERNANDO; MILBEIER, ROZIMERLI R.; PEREIRA, TANIA M. (Salão do Conhecimento, 2013)
Resumo